Biocompatible Supramolecular Mesoporous Silica Nanoparticles as the Next-Generation Drug Delivery System - Mohamed, Farahidah; Oo, May K.; Chatterjee, Bappaditya; Alallam, Batoul (Frontiers in Pharmacology, 2022)
Supramolecular mesoporous silica nanoparticles (MSN) offer distinct properties as opposed by micron-sized silica particles in terms of their crystal structure, morphology-porosity, toxicity, biological effects and others. MSN biocompatibility has touched pharmaceutical realm to exploit its robust synthesis pathway for delivery of various therapeutic molecules including macromolecules and small molecule drugs. This article provides a brief review on MSN history followed by special emphasis on the influencing factors affecting morphology-porosity characteristics. Its applications as the next-generation drug delivery system (NGDDS) particularly in controlled release dosage form via oral drug delivery system are also presented and shall be highlighted as oral delivery is the most convenient route of drug administration with economical cost of development through to scale-up for clinical trials and market launch.